An Analysis of Christopher Alexander's Understanding of Religious Architecture through the Study of 'Face of God' from the Fourth Volume of His Nature of Order - Seyedeh Mahsa Bagheri; Mahmoud Arzhmand; Seyed Behshid Hosseini (صفه)
Looking at the history of architectural theories, and with reference to the opinions of thinkers, one can see architecture and rhetoric as mutually related throughout history. It seems that reflecting on this relationship can open up new horizons for architectural thought. But the changing meaning of rhetoric has resulted in a variety of relationship levels, resulting in different gifts for architecture.This paper starts with an exploration three different levels of relationships, resulting from three corresponding understandings of rhetoric. The first defines rhetoric as communication, the second as the art of speaking. But the third emanates from the thoughts of those design scholars who, whilst contemplating rhetorical relations and design matters, do not see use rhetoric as speech, communication or the art of speaking, but as an art of composition. From this point of view, rhetoric and architecture are both knowledges of composition. This paper argues that the latter has opened the door to the deepest understandings of rhetorical knowledge and the most fruitful link between rhetoric and architecture. In response to the haphazard literature associated with this view, the paper expands on rhetoric as 'the art of composition', and then moves on to identify three levels of rhetoric composition, namely, composing people's horizons (conviction), knowledges and insights. The important issue of architecture today, the paper argues, is the lack of shared horizons between architects and their audiences, as well as the lack of coherence between the various architectural knowledges and insights. By understanding rhetoric as the art of composition and linking architecture and rhetoric in the light of this understanding, one can look at architecture from a different perspective and restore the missing coherence in architecture.